Study on the microstructural evolution mechanism of the angular contact ball bearing rings during the quenching and tempering process - Ruijie Gu; Yi Tong; Qiang Wang; Liaoyuan Chen; Ziyang Shang (Scientific Reports)
Abstract Since the rings of the angular contact ball bearings (ACBBs) are typical highly sensitive quenching thin-walled structure, the microstructure and properties variation of the rings during the heat treatment process are often difficult to be controlled precisely, and then the service life of the bearings is reduced. Therefore, in this study, the combination of the numerical simulation and experimental was carried out during the quenching and tempering process of ACBBs (7008C), the phase transformation of the inner and outer ring during the heat treatment process were explored, and the law of the microstructure evolution and the mechanical properties variation were revealed. Firstly, based on the multi-field coupling theory of temperature, microstructure and stress–strain field, the numerical simulation model of the heat treatment process of the bearing rings was established. Secondly, the content of each element of the rings was measured by a direct reading spectrometer (SPECTRO M12), and the thermophysical characteristics parameters of the material were calculated by the JMatPro software. Besides, the numerical simulation of the process was carried out by the Deform software. The evolution process of the temperature, microstructure, and properties during the heat treatment of the rings was investigated. Finally, the microstructure and mechanical properties of the heat-treated rings were obtained by optical microscopy, SEM and hardness tester. The results showed that the microstructure of the inner and outer ring after heat treatment process was cryptocrystalline martensite, and the average sizes of spherical carbides precipitated at grain boundaries were 0.39 μm and 0.38 μm, and corresponding hardnesses were increased to be 62.5 HRC and 62.7 HRC. The evolution of temperature-microstructure-mechanical properties during the heat treatment process of the ACBB rings are revealed, which can provide an important theoretical and technological support for the heat treatment process of the bearing rings for high-quality production.